217 Altered Regulation of the Inhibitor IÎºBÎ± Contributes to Changes in NF-ÎºB Regulated Genes in the TILRR ko Mouse. (6th June 2015) - Smith, Sarah; Samokhin, Andriy; Murphy, Emer; Francis, Sheila; Qwarnstrom, Eva
Abstract : Introduction: Inflammatory responses are key drivers in the pathogenesis of atherosclerosis. We have identified a co-receptor, TILRR, a prominent activator of NF-ÎºB controlled responses, which we have demonstrated is highly expressed in atherosclerotic lesions. Using Apoe –/– (Apo-lipoprotein E knockout) mice we have recently shown that administration of a blocking peptide antibody, which selectively targets amplification of inflammatory responses through TILRR, significantly reduces progression of atherosclerosis and promotes plaque stability. This study examines the molecular mechanisms underlying the reduced NF-ÎºB activation in the TILRR knockout mouse. Methods and results: Microarray analysis of blood and spleen monocytes from TILRR knockout mice and littermate controls, revealed pronounced reductions in NF-ÎºB controlled inflammatory genes relevant to development of cardiovascular disease including Cathepsin L1, CXCL1 and CXCL13. Western analysis demonstrated a 65% decrease in IÎºBÎ± expression and a 60% reduction in inhibitor degradation in IL-1 stimulated monocytes from TILRR-/- mice compared to responses in littermate controls. Parallel in vitro studies were carried out to determine the underlying mechanisms and consequences of these changes on interaction of the inhibitor with NF-ÎºB. Deletion of the ANK 2 region of IÎºBÎ± resulted in loss of function while the impact of ANK deletions 3, 4, and 5 was not significantly different from the wild type protein. 3-D modelling of the ANK2 deleted protein revealed that the modified protein maintained its overall structure. The modified protein lost its ability to interact with NF-ÎºB, identifying a role for this region in IkBa/NF-kB complex formation. Ongoing studies are evaluating alanine-scanning mutants of conserved residues within the ANK2 region to determine their impact on amplified NF-kB responses. Conclusion: Our results are consistent with a role for TILRR in regulation of NF-ÎºB controlled inflammatory gene activation in vivo, and suggest that functional alterations in IÎºBÎ± regulation in part are responsible for the reductions in the inflammatory response.